Amoeboid form of Blastocystis hominis - a detailed ultrastructural insight - Tan, T.C.; Suresh, K.G. (2006)
The amoeboid form of Blastocystis hominis has been reported infrequently, and its morphological descriptions have yielded conflicting and confusing reports. In the present study, we used the amoeboid forms seen predominantly in symptomatic patients infected with Blastocystis to provide detailed descriptions on the fine surface structure and intracellular morphology. Scanning electron microscopy revealed the irregular shape of the amoeboid form, with an intercalated fibrillar structure and a highly convoluted surface with deep indentations and projected pseudopodia. Transmission electron microscopy showed the existence of two types of amoeboid forms of B. hominis in in vitro culture, one with a large central vacuole containing tiny electron-dense particles while the other contains multiple small vacuoles in the cytoplasm. A surface coat with varying thickness surrounded the amoeboid form, which also showed prominent, extended pseudopodia of varying shape. Irregularly shaped mitochondrion-like organelles with prominent cristae, lipid inclusions, and multiple vacuoles were frequently seen in close proximity with the pseudopodia. The characteristic nucleus with a crescentic band of electron-dense chromatin material was also seen.